Association of 25-Hydroxyvitamin D Deficiency in Pediatric Epileptic Patients - CHAUDHURI, Jaydip Ray CHAUDHURI; MRIDULA, Kandadai Rukmini; RATHNAKISHORE, Chakrala; BALARAJU, Banda; BANDARU, VSC Srinivasarao (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Chaudhuri IR, Mridula KR, Rathnakishore Ch, Balaraju B, Bandaru VCS. Association of 25-Hydroxyvitamin D Deficiency in Pediatric Epileptic Patients. Iran J Child Neurol. Spring 2017; 11(2):48-56. Abstract Objective Epilepsy is a chronic neurological disorder requiring long-term therapy using antiepileptic medications. Reports have incriminated long-term antiepileptic drugs use in deficiency of vitamin D and bone diseases in all age groups. We aimed to investigate the association between serum 25-hydroxyvitamin D levels and pediatric epilepsy in Indian patients. Materials & Methods We prospectively recruited 100 pediatric epilepsy patients, on monotherapy for minimum one-year duration, and 50 age and sex matched controls. This study was carried out at Yashoda Hospital, India from 2011-2014. All cases and controls underwent tests for serum 25-hydroxyvitamin D, alkaline phosphatase, serum calcium and phosphorus levels. Results Patients with 25-hydroxyvitamin D deficiency were significantly higher among cases (45%) than controls (24%). Mean alkaline phosphatase was significantly higher in cases and mean serum calcium was significantly lower (8.3±1.5) in cases. Amongst antiepileptic drugs, carbamazepine and sodium valproate were significantly associated with 25-hydroxyvitamin D deficiency. Risk of vitamin D deficiency was highest with sodium valproate usage (odds:4.0;95%CI 1.4-11.6) followed by carbamazepine use (odds: 2.7; 95%CI 1.0-6.8). After adjustment using multiple logistic regression, antiepileptic drugs showed independent association with 25-hydroxyvitamin D deficiency (odds:2.2;95%CI 0.9-4.5). Conclusion 25-hydroxyvitamin D deficiency was significantly associated with use of carbamazepine and sodium valproate in pediatric epilepsy. References 1. Santhosh NS, Sinha S, Satishchandra P. Epilepsy: Indian perspective. Ann Indian Acad Neurol2014;17(Suppl 1):S3-11. 2. Sridharan R, Murthy BN. Prevalence and pattern of epilepsy in India. Epilepsia 1999;40:631-66. 3. RainaSK,RazdanS,NandaR.Prevalence of neurological disorders in children less than 10 years of age in RS Pura town of Jammu and Kashmir. J Pediatr Neurosci 2011; 6:103-05. 4. Misra A, Aggarwal A, Singh O, Sharma S. Effect of carbamazepine therapy on vitamin D and parathormone in epileptic children. Pediatr Neurol 2010 Nov;43:320- 24. 5. Lazzari AA, Dussault PM, Thakore-James M, Gagnon D, Baker E, Davis SA et al.Prevention of bone loss and vertebral fractures in patients with chronic epilepsy-antiepileptic drug and osteoporosis prevention trial. Epilepsia 2013;54:1997-2004. 6. Menon B, Harinarayan CV. The effect of anti epileptic drug therapy on serum 25-hydroxyvitamin D and parameters of calcium and bone metabolism a longitudinal study. Seizure 2010;19:153-58. 7. Chaudhuri JR, Mridula KR, Alladi S, Anamika A, Umamahesh U, Balaraju B et al. Serum 25-hydroxyvitamin D deficiency in ischemic stroke and subtypes in Indian patients. J Stroke 2014;16:44-50. 8. Fisher RS, van Emde Boas W, Blume W, Elger C, Genton P, Lee P, et al. Epileptic seizures and epilepsy: definitions proposed by the International League Against Epilepsy (ILAE) and the International Bureau for Epilepsy (IBE). Epilepsia 2005;46:470-72. 9. Chaudhuri JR, Mridula KR, Anamika A, Boddu DB, Misra PK, Lingaiah A et al. Deficiency of 25-hydroxyvitamin d and dyslipidemia in Indian subjects. J Lipids 2013;2013:623420. 10. Gniatkowska-Nowakowska A. Fractures in epilepsy children. Seizure 2010;19:324-25. 11. Shellhaas RA, Barks AK, Joshi SM. Prevalence and risk factors for vitamin D insufficiency among children with epilepsy. Pediatr Neurol 2010;42:422-26. 12. Nettekoven S, Strohle A, Trunz B, Wolters M, Hoffmann S, Horn R, et al. Lichtinghagen R, Welkoborsky HJ, Tuxhorn I, Hahn A. Effects of antiepileptic drug therapy on vitamin D status and biochemical markers of bone turnover in children with epilepsy. Eur J Pediatr 2008;167:1369-77. 13. Rajantie J, Lamberg-Allardt C, Wilska M. Dose carbamazepine treatment lead to need of extera vitamin D in some mentally retarded children. Acta Pediatr Scand 1984;73:325-28. 14. Jekovec-Vrhovsek M, Kocijancic A, Prezelj J. Effect of vitamin D and calcium on bone mineral density in children with CP and epilepsy in full-term care. Dev Med Child Neurol 2000;42:403-05. 15. Pack AM. The Association between Antiepileptic Drugs and Bone Disease. Epilepsy Currents 2003; 3:91-95. 16. Babayigit A, Dirik E, Bober E, Cakmakci H. Adverse effects of antiepileptic drugs on bone mineral density. Pediatr Neurol 2006;35:177-81. 17. Pack AM. The impact of long-term antiepileptic drug use on bone health. Advanced Students 2005;5:S567-71. 18. Voudris KA, Attilakos A, Katsarou E, Garoufi A, Dimou S, Skardoutsou A,et al. Early alteration in bone metabolism in epileptic children receiving carbamazepine monotherapy owing to the induction of hepatic drug-metabolizing enzymes. J Child Neurol 2005; 20: 513-16. 19. Malik R, Mohapatra JN, Kabi BC, Halder R. 5 Hydroxy Cholecalciferol Levels in Infants with Hypocalcemic Seizures J Nutr Food Sci 2014; 4:3 20. Razazizan N, Mirmoeini M, Daeichin S, Ghadiri K. Comparison of 25-hydroxy vitamin D, calcium and alkaline phosphatase levels in epileptic and non-epileptic children. Acta Neurol Taiwan 2013;22:112-16. 21. Krishnamoorthy G, Karande S, Ahire N, Mathew L, Kulkarni M. Bone Metabolism Alteration on Antiepileptic Drug Therapy. Indian J Pediatr 2009; 76 : 377-83. 22. Valsamis HA, Arora SK, Labban B, McFarlane SI.Antiepileptic drugs and bone metabolism. Nutr Metab (Lond) 2006;3:36 23. MintzerS, Boppana P, Toguri J, DeSantis A. Vitamin D levels and bone turnover in epilepsy patients taking carbamazepine or oxcarbamazepine. Epilepsia 2006;47:510-15. 24. Pack AM, Morrell MJ. Adverse effect of antiepileptic drug on bone structure: Epidemiology mechanisms and therapeutic indications.CNS Drugs 2001;15:633-42. 25. Yaghini O, Tonekaboni SH, Amir Shahkarami SM, Ahmad Abadi F, Shariat F, Abdollah Gorji F. Bone mineral density in ambulatory children with epilepsy. Indian J Pediatr 2015;82:225-29. 26. Verrotti A, Greco R, Morgese G, Chiarelli F. Increased bone turnover in epileptic patients treated with carbamazepine. Ann Neurol 2000;47: 385-88. 27. Ginige N,de Silva KSH, Wanigasinghe JK, Gunawardane NS, Munasinghe TMJ. Effects of long term anti epileptic drugs on serum vitamin D levels and bone profile in a cohort of Sri Lankan children. Int J Pediatr Endocrinol 2015,2015(Suppl 1):P66. 28. Hosseinpour F, Ellfolk M, Norlin M, Wikvall K. Phenobarbital suppresses vitamin D3 25-hydroxylase expression: a potential new mechanism for drug-induced osteomalacia. Biochem Biophys Res Commun 2007;357:603-07. 29. Heo K, Rhee Y, Lee HW, Lee SA, Shin DJ, Kim WJ, et al. The effect of topiramate monotherapy on bone mineral density and markers of bone and mineral metabolism in premenopausal women with epilepsy. Epilepsia 2011;52:1884-89. 30. Zhou C, Assem M, Tay JC, Watkins PB, Blumberg B, Schuetz EG, et al.Steroid and xenobiotic receptor and vitamin D receptor crosstalk mediates CYP24 expression and drug-induced osteomalacia. J Clin Invest 2006;116:1703-12. 31. Pascussi JM, Robert A, Nguyen M, Walrant-Debray O, Garabedian M, Martin P, et al.. Possible involvement of pregnane X receptor-enhanced CYP24 expression in drug-induced osteomalacia. J Clin Invest 2005;115:177- 86. 32. Holick MF. Stay tuned to PXR: an orphan actor that may not be D-structive only to bone. J Clin Invest 2005;115:32- 4. 33. Perucca E. Clinical implications of hepatic microsomal enzyme induction by antiepileptic drugs. Pharmacol Ther 1987;33:139-44. 34. Koch HU, Kraft D, von Herrath D, Schaefer K. Influence of diphenylhydantoin and phenobarbital on intestinal calcium transport in the rat. Epilepsia 1972;13:829-41. 35. Weinstein RS, Bryce GF, Sappington LJ, King DW, Gallagher BB. Decreased serum ionized calcium and normal vitamin D metabolite levels with anticonvulsant drug treatment. J Clin Endocrinol Metab 1984;58:1003-09. 36. Onodera K, Takahashi A, Sakurada S, Okano Y. Effects of phenytoin and/or vitamin K2 (menatetrenone) on bone mineral density in the tibia of growing rats. Life Sci 2002; 70: 1533-42. 37. Vernillo AT, Rifkin BR, Hauschka PV. Phenytoin affects osteoblastic secretion from osteoblastic rat osteosarcoma 17/2.8 cells in culture. Bone 1990;11:309-12. 38. Guo C, Ronen GM, Atkinson SA. Long-term valproate and lamotrigine treatment may be a marker for reduced growth and bone mass in children with epilepsy. Epilepsia 2001; 42:1141-47. 39. Nakken KO, Tauboll E. Bone loss associated with use of antiepileptic drugs. Expert Opin Drug Saf 2010;9:561-71. 40. Lee RH,Lyles KW, Colon-Emeric C. A review of the effect of anticonvulsant medications on bone mineral density and fracture risk. Am J Geriatr Pharmacother 2010; 8:34-46. 41. Teagarden DL, Meador KJ, Loring DW. Low vitamin D levels are common in patients with epilepsy. Epilepsy Res 2014;108:1352-56. 42. Wu FJ, Sheu SY, Lin HC. Osteoporosis is associated with antiepileptic drugs: a population-based study. Epileptic Disord 2014;16:333-42. 43. Cansu A, Yesilkaya E, Serdaroglu A, Hirfanoglu TL, Camurdan O, Gulbahar O, et al. Evaluation of bone turnover in epileptic children using oxcarbazepine. Pediatr Neurol 2008;39:266-71. 44. Bergqvist AG, Schall JI, Stallings VA. Vitamin D status in children with intractable epilepsy, and impact of the ketogenic diet. Epilepsia 2007;48:66-71. 45. Nicolaidou P, Georgouli H, Kotsalis H, Matsinos Y, Papadopoulou A, Fretzayas A, et al.Effects of anticonvulsant therapy on vitamin D status in children: Prospective monitoring study. J Child Neurol 2006;21:205-09. 46. Farhat G, Yamout B, Mikati MA, Demirjian S, Sawaya R, El-Hajj Fuleihan G. Effect of antiepileptic drugs on bone density in ambulatory patients. Neurol 2002;58:1348-53. 47. Harijan P, Khan A, Hussain N. Vitamin D deficiency in children with epilepsy: Do we need to detect and treat it? J Pediatr Neurosci 2013;8:5-10. 48. Mikati MA, Dib L, Yamout B, Sawaya R, Rahi AC, Fuleihan Gel-H. Two randomized vitamin D trials in ambulatory patients on anticonvulsants: Impact on bone. Neurol 2006; 67:2005-14. 49. Bianchini G, Mazzaferro S, Mancini U, Bianchi AR, Donato G, Massimetti C,et al.Calcium phosphorus changes in chronic anticonvulsant therapy: effects of administration of 25 hydroxy vitamin D3 on secondary hyperparathyroidism. Acta Vitaminol Enzymol 1983;5:229-34. 50. Drezner MK. Treatment of anticonvulsant drug – induced bone disease. Epilepsy Behav 2004;5:S41-7. 51. Howard JM. Anticonvulsant induced bone disease. Editorial. Arch Neurol 2004;58:1352-53.